Social Media as a Tool for Islamic Dawah in the Digital Era: Analyzing the Benefits and Obstacles - Sofwan Manaf; Rokimin Rokimin; Miftah Hur Rahman; Zahid Zufar At Thaariq; Muhamad Towil Akhirudin (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2026)
The digital transformation has fundamentally altered the landscape of Islamic dawah (preaching). However, existing studies remain fragmented across isolated platforms, specific demographics, or singular aspects of digital religious communication, lacking an integrated analytical framework that systematically maps the interrelationship between benefits, obstacles, and mitigation strategies. This qualitative study addresses this gap by conducting a systematic literature review (SLR) following the PRISMA protocol, synthesizing findings from 35 peer-reviewed articles published between 2022 and 2025, sourced from Scopus-indexed journals and Indonesian SINTA-accredited publications (SINTA 2–4). Employing thematic analysis based on the Braun and Clarke framework, this research identifies four categories of benefits (expanded reach transcending geographical boundaries, enhanced youth engagement, interactive religious discourse, and democratization of religious knowledge), four categories of obstacles (misinformation proliferation, content verification challenges, commercialization of religious messages, and algorithmic barriers), and three strategic responses (strategic content planning, ethical guidelines adherence through Maqasid al-Shariah, and multi-stakeholder collaboration). The study proposes an original Digital Dawah Ecosystem Framework that conceptualizes the dialectical relationship between enabling and constraining factors in digital religious communication, revealing a "digital dawah paradox" in which the same platform affordances that facilitate expanded outreach simultaneously create conditions for misinformation and content distortion. Theoretically, this study extends the Uses and Gratifications Theory into the domain of religious digital communication. It contributes to the Mediatization of Religion theory by demonstrating how platform logics reshape dawah practices. Practically, the findings offer an operationalized strategic model for dawah practitioners, religious institutions, policymakers, and platform operators seeking to optimize digital religious communication while maintaining Islamic ethical integrity.